Pengaruh Spesifikasi Tugas, Pola Koordinasi, dan Motivasi Terhadap Kinerja Pegawai di Lingkungan Kantor Kecamatan Kartasura (Studi Kasus: Kantor Kecamatan Kartasura, Kabupaten Sukoharjo) - Rakaditya Nugraha; Supawi Pawenang; Sarsono Sarsono (JURNAL ILMIAH EDUNOMIKA, 2020)
This study a medito analyze the impactoof job spesification, coordination pattern and motivation on employee performance. The sample was the employee of the Kantor Kecamatan Kartasura totaling 35 respondents. Regression analysis technique were use to analyze the impact of job spesification, coordination pattern, and motivation of the employee performance is by using SPSS. The analysis showed that the job spesification have significantppositivepeffectpon employeepperformance. The analysis also showed that coordination pattern significant influence onpemployeepperformance. Andpmotivation significant positive influence onpemployeepperformance.Thepcontribution ofpthe three independent variables on employee performance is 76,2 %. Keywords: job specification, coordination pattern, motivation